1995
DOI: 10.1007/bf02179255
|View full text |Cite
|
Sign up to set email alerts
|

Scaling, propagation, and kinetic roughening of flame fronts in random media

Abstract: We introduce a model of two coupled reaction-diffusion equations to describe the dynamics and propagation of flame fronts in random media. The model incorporates heat diffusion, its dissipation, and its production through coupling to the background reactant density. We first show analytically and numerically that there is a finite critical value of the background density, below which the front associated with the temperature field stops propagating. The critical exponents associated with this transition are sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…Indeed, in the absence of nucleation it has been shown in Ref. [10] that the flame front roughens according to the KPZ interface equation, through which some of these correspondences can be made.…”
Section: Figmentioning
confidence: 92%
See 4 more Smart Citations
“…Indeed, in the absence of nucleation it has been shown in Ref. [10] that the flame front roughens according to the KPZ interface equation, through which some of these correspondences can be made.…”
Section: Figmentioning
confidence: 92%
“…Such continuum reaction-diffusion equations have been used extensively in physics, chemistry, biology and engineering to describe a wide range of phenomena from pattern formation to combustion. However, the connection of reaction-diffusion equations to nucleation and interface growth has received little attention.In a recent study of slow combustion in disordered media, Provatas et al [9,10] showed that flame fronts exhibit a percolation transition, consistent with mean field theory, and that the kinetic roughening of the reaction front in slow combustion is consistent with the KardarParisi-Zhang (KPZ) [11] universality class. In this paper we make a further connection between slow combustion started by spontaneous fluctuations, and the classical theory of the nucleation and growth of droplets from a metastable phase.…”
mentioning
confidence: 84%
See 3 more Smart Citations